Aspects of the zonally asymmetric Southern Hemispheric Circulation and Representation in the MPI Earth System Model - Babian, Stella (2018)
Due to the characteristic land-sea distribution of the southern hemisphere (SH) its atmospheric circulation is generally more zonally symmetric than its northern hemispheric equivalent. Distinct deviances from its symmetric nature, however, play an important role with regard to weather and climate on the regional scale, e.g. on the Antarctic sea ice distribution over the Amundsen Sea (Lefebvre et al., 2004). Thus the SH represents an ideal research area for the investigation of different aspects of the zonally asymmetric components of the circulation. As the Antarctic Oscillation (AAO) is the leading mode of tropospheric variability an adequate representation in earth system models is essential. Therefore the first goal of this thesis is evaluating to what extent the AAO and its related precipitation patterns are represented in the MPI Earth System Model (MPI-ESM). This is done by comparing the spatial patterns of the AAO (given as EOFs) with their associated principal components (PCs) and precipitation patterns of the MPI-ESM to three different reanalyses. A comparison between the leading EOFs of the MPIESM and ERA-Interim indicates shifted and less pronounced centers of action in the MPI-ESM. Similarly the spectral density estimates of the associated PCs in the ESM show reduced variability for periods between 4 to 5 months. The relation between AAO and SH precipitation is assessed via composite and correlation analysis. Altogether the MPI-ESM underestimates the relation of AAO and SH precipitation but exhibits the same sign and spatial distribution of correlation values. These findings suggest a lack of El Nino-Southern Oscillation (ENSO) variability in the MPI-ESM and related teleconnections towards Antarctica, which accounts for the reduced variability over the Amundsen Sea. One of the most prominent asymmetric features of the SH circulation is the split jet over Australia and New Zealand in Austral winter. Previous studies have developed indices to describe to what degree the upper-level mid-latitude ...